2016
DOI: 10.1055/s-0036-1581993
|View full text |Cite
|
Sign up to set email alerts
|

Sporadic Cerebral Amyloid Angiopathy: Pathophysiology, Neuroimaging Features, and Clinical Implications

Abstract: Sporadic cerebral amyloid angiopathy is a small vessel disorder defined pathologically by progressive amyloid deposition in the walls of cortical and leptomeningeal vessels resulting from disruption of a complex balance between production, circulation, and clearance of amyloid-β peptide (Aβ) in the brain. Cerebral amyloid angiopathy is a major cause of lobar symptomatic intracerebral hemorrhage, transient focal neurologic episodes, and a key contributor to vascular cognitive impairment. The mechanisms and cons… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
44
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 48 publications
(47 citation statements)
references
References 112 publications
(131 reference statements)
3
44
0
Order By: Relevance
“…We observed Aβ 1-42 plaques, mainly in the form of diffuse plaques, but some large compact plaques were also detected in the parenchyma. Aβ 1-40 diffuse plaques were present mainly around blood vessels as already described for cerebral amyloid angiopathy (CAA) in humans (Boulouis et al, 2016); however, Aβ 1-40 compact plaques were not observed. No Aβ staining was observed in younger animals.…”
Section: Discussionsupporting
confidence: 61%
“…We observed Aβ 1-42 plaques, mainly in the form of diffuse plaques, but some large compact plaques were also detected in the parenchyma. Aβ 1-40 diffuse plaques were present mainly around blood vessels as already described for cerebral amyloid angiopathy (CAA) in humans (Boulouis et al, 2016); however, Aβ 1-40 compact plaques were not observed. No Aβ staining was observed in younger animals.…”
Section: Discussionsupporting
confidence: 61%
“…Acquired and non-acquired disease states such as stroke, Alzheimer’s disease and others are associated with abnormal vascular function 19,20 . While extensive literature exists on stroke and its vascular effects/defects, there are scant reports related to traumatic brain injury (TBI).…”
Section: Discussionmentioning
confidence: 99%
“…Sporadic cerebral amyloid angiopathy (CAA) is a very common small vessel disease (SVD) of the brain, a key cause of spontaneous lobar intracerebral haemorrhage (ICH) and a potential contributor to age- and Alzheimer pathology-related cognitive decline (Boulouis et al, 2016, Charidimou et al, 2012a, Viswanathan and Greenberg, 2011). CAA has thus received increasing attention in the both the Alzheimer and the stroke community for a number of additional important clinical reasons.…”
Section: Introductionmentioning
confidence: 99%
“…While the clinical-imaging spectrum of CAA has been expanded and refined substantially with the broad availability of brain MR imaging (Boulouis et al, 2016), imaging biomarkers of brain parenchymal microvascular lesions provide only indirect evidence for the disease. Since symptomatic or asymptomatic CAA presentations with or without ICH are becoming increasingly common clinical scenaria, additional non-invasive techniques and more direct biomarkers to diagnose CAA in vivo would have major clinical impact.…”
Section: Introductionmentioning
confidence: 99%